Morphological modifications in soybean in response to soil water management - Gonçalves, Clebson Gomes [UNESP]; da Silva Junior, Antonio Carlos [UNESP]; Pereira, Maria Renata Rocha; Gasparino, Eduardo Custódio [UNESP]; Martins, Dagoberto [UNESP] (Springer Nature, 2017)
Water shortage is the most limiting abiotic stress for agricultural crops, and the mechanisms through which plants perceive water restriction are highly complex and must be better understood. In order to shed light on the effect of hydric stress over the anatomical characteristics of soybean, this paper aimed to examine the morphological alterations in two soybean cultivars: MG/BR 46 Conquista (non-transgenic) and BRS Valiosa RR (transgenic), via the response to different soil water managements, in two vegetative development stages. The plants were subjected to five soil water hydric management conditions (Ψs): −0.03; −0.05; −0.07; −0.5; −1.5 MPa, in vegetative development stages V2 and V4. Evaluations were carried out involving stomatal conductance, leaf area, leaf anatomy measures (width of palisade and spongy parenchyma, length of central vein, adaxial and abaxial width of central vein, length of vascular bundle, width of vascular bundle), and stem diameter. A higher tolerance was observed in BRS Valiosa RR to moderate hydric deficit conditions when they occurred in soybean stage V2. The BRS Valiosa RR cultivar presents a better morphologically and anatomically adaptive response to moderate hydric restrictions of up to (−0.07 MPa) when they occur in the first weeks of plant development.
Keywords: Anatomy; Drought tolerance; Glycine Max; Stomatal conductance